The effect of local propolis irrigation as an adjunct to scaling and root planning on alveolar bone loss in experimental periodontitis in rats (A biochemical and histological study). - Khadeeja Mohammed Ali; Zewar Ahmad Saleh; Jalal Ali Jalal (Erbil Dental Journal)
Background and objectives: The present study aimed to investigate the efficacy of local use of propolis (PRO) as adjunctive to scaling and root planing (SRP) in the treatment of alveolar bone loss in rats with ligature induced periodontitis (LIP). Material and methods: 60 male rats were divided into three groups of 20 rats: the control group (C) with no experimental periodontitis or treatment (gp1); ligature-induced periodontitis treated by SRP with a vehicle irrigation (dimethyl sulfoxide + physiological saline solution) group (gp2); and ligature-induced periodontitis treated by SRP with 10% PRO extract irrigation group (gp3). The irrigation materials were locally applied three times daily for 11 days After removal of the ligature, SRP was performed in gp2 and gp3. Five rats from each group were euthanized on days 0, 7, 14, and 21 after local treatment. Intracardiac blood samples and mandible were obtained for biochemical and histopatholical analysis. Results: Rats that received local treatment by SRP with propolis irrigation in gp3 revealed features of acceleration of the periodontal tissue-repair process, alveolar bone formation, and significantly higher alkaline phosphatase serum levels (ALP) than gp2 were treated by SRP with vehicle irrigation. Conclusion: Local use of propolis as an adjunct therapy to SRP can be effective in the treatment of alveolar bone loss in rat model of ligature-induced periodontitis.